Search for Cytolethal Distending Toxin Production among Fecal Escherichia Coli Isolates from Brazilian Children with Diarrhea and without Diarrhea - Lilian Regina Macelloni Marques; Ana Terezinha Tavechio; Cecília M. Abe; Tânia A. T. Gomes (2003)
ABSTRACT The enteropathogenic role of cytolethal distending toxin-producing Escherichia coli was investigated by searching sequences homologous to the cdt genes of an O86 strain among 2,074 isolates from 200 children with acute diarrhea and 200 controls in Brazil. Only one (0.5%) diarrheic child and two (1.0%) nondiarrheic controls harbored cdt -positive isolates.